Rooting of yellow mombin cuttings (Spondias mombin L.) as a function of the application of plant regulators (2018)
At the moment, there are no commercial  yellow mombin crops in Brazil, where fruits are harvested from extractive crops. One reason for this is the lack of a  propagation protocol for this species because the yellow mombin has a low rooting percentage for cuttings. Therefore, techniques that provide maximum rooting for cuttings are required. The objective of this study was to evaluate the effect of a matrix plant treatment with zinc on the rooting of yellow mombin cuttings treated with indolebutyric acid. In this experiment, a completely randomized design was used, with 9 treatments  arranged with pre-determined levels for the factors with  the matrix "Central Box Compound" for the zinc concentrations (0, 5.8, 20, 34.2 and 40 mg L-1) and combinations with the indolbultric acid concentrations (0, 872.35, 3000, 5127.65 and 6000 mg L-1), with 4 replicates, where each experiment unit consisted of 12 cuttings. The application of zinc in yellow mombin matrix plants had no effect on the rooting of cuttings. The 6000 mg L-1  indolebutyric acid dose provided an increase in sprouts and live cuttings with a callus; however, it did not influence the rooting.